Effect of esketamine on postoperative depressive symptoms in patients undergoing thoracoscopic lung cancer surgery: A randomized controlled trial - Gan, Shu-lin; Long, Yu-qin; Wang, Qin-yun; Feng, Chang-dong; Lai, Chen-xu; Liu, Chun-tong; Ding, Yun-ying; Liu, Hong; Peng, Ke; Ji, Fu-hai (Frontiers in Psychiatry, 2023)
Background: Depressive symptoms are common among patients with lung cancer. We aimed to assess the effects of esketamine on postoperative depressive symptoms after thoracoscopic lung cancer surgery. Methods: In this randomized, double-blind, placebo-controlled trial, 156 patients undergoing thoracoscopic lung cancer surgery were randomly allocated in a 1:1 ratio to receive intravenous esketamine (intraoperatively and in patient-controlled analgesia until 48 h postoperatively) or normal saline placebo. The primary outcome was the proportion of patients with depressive symptoms at 1 month postoperatively, assessed using the Beck Depression Inventory-II (BDI-II). Secondary outcomes included depressive symptoms at 48 h postoperatively, hospital discharge and 3 months postoperatively, BDI-II scores, anxious symptoms, Beck Anxiety Inventory scores, Quality of Recovery-15 (QoR-15) scores, and 1- and 3-month mortality. Main results: A total of 151 patients (75 in the esketamine group and 76 in the normal saline group) completed the 1-month follow-up. The esketamine group had a significantly lower incidence of depressive symptoms at 1 month compared to the normal saline group (1.3% vs. 11.8%; risk difference = -10.5%, 95%CI = -19.6% to -0.49%; P = 0.018). After excluding patients without lung cancer diagnosis, the incidence of depressive symptoms was also lower in the esketamine group (1.4% vs. 12.2%; risk difference = -10.8%, 95%CI = -20.2% to -0.52%; P = 0.018). The secondary outcomes were similar between groups, except that the esketamine group had higher QoR-15 scores at 1 month postoperatively (median difference = 2; 95%CI = 0 to 5; P = 0.048). The independent risk factors for depressive symptoms were hypertension (odds ratio = 6.75, 95%CI = 1.13 to 40.31; P = 0.036) and preoperative anxious symptoms (odds ratio = 23.83, 95%CI = 3.41 to 166.33; P = 0.001). Conclusions: Perioperative administration of esketamine reduced the incidence of depressive symptoms at 1 month after thoracoscopic lung cancer surgery. History of hypertension and preoperative anxious symptoms were independent risk factors for depressive symptoms.